The German Minimum Wage: Experiences and perspectives after one year - Marc Amlinger; Reinhard Bispinck; Thorsten Schulten (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2016)
Since 1 January 2015 a statutory minimum wage of exteuro 8.50 per hour applies in Germany. In 2014 between 4.8 and 5.4 million employees still earned a lower hourly wage. Even if it cannot yet be stated exactly how many employees benefitted from the introduction of the minimum wage, above-average wage increases in the classical low-wage sectors indicate significant effects of the introduction of the minimum wage. Even collective bargaining policies benefitted from the introduction of a minimum wage and contributed to the further increase of the lowest wage groups. The negative effects on the labour market that were predicted by many economists did not materialise. On the contrary, employment in Germany has seen a continuous increase. Merely the so-called 'mini jobs' (a special form of marginal part-time employment) show a strong decline, but many of these were transformed into regular jobs requiring social insurance. Against the background of these positive experiences, discussions are currently being held on the future adjustment of the minimum wage that is to come into effect at the beginning of 2017. Following the German Minimum Wage Act the Minimum Wage Commission - composed by employers and trade union representatives - has to give a recommendation by taking into account the recent developments of collectively agreed wages. According to the wage index of the Federal Statistical Office, collectively agreed wages increased by a total of about 5.5% in 2014 and 2015. Thus, the minimum wage would have to be increased to about exteuro 9. Furthermore, it should be examined whether this level of the minimum wage actually guarantees "appropriate minimum protection for employees", as required by the Minimum Wage Act. – – Seit dem 1. Januar 2015 gilt in Deutschland ein gesetzlicher Mindestlohn von 8,50 Euro pro Stunde. Noch im Jahr 2014 hatten zwischen 4,8 und 5,4 Millionen Beschäftigte einen geringeren Stundenlohn. Auch wenn sich bislang noch nicht exakt sagen lässt, wie viele Beschäftigte letztendlich von der Einführung des Mindestlohns profitiert haben, so deuten die überdurchschnittlich hohen Lohnsteigerungen in klassischen Niedriglohnbranchen auf erhebliche Mindestlohneffekte hin. Auch die Tarifpolitik hat von der Einführung des Mindestlohns profitiert und dazu beigetragen, dass die untersten Lohngruppen weiter angehoben wurden. Die von vielen Ökonomen befürchteten negativen Auswirkungen auf den Arbeitsmarkt sind dagegen ausgeblieben. Die Beschäftigung in Deutschland hat im Gegenteil kontinuierlich zugenommen. Lediglich bei den Minijobs ist ein starker Rückgang beobachtbar, wobei hier ein erheblicher Anteil in sozialversicherungspflichtige Arbeitsplätze umgewandelt wurde. Vor dem Hintergrund der positiven Erfahrungen wird derzeit über die zukünftige Anpassung des Mindestlohns diskutiert, die erstmals Anfang 2017 erfolgen soll. Als Orientierungsgröße für die Empfehlung der Mindestlohnkommission soll laut Mindestlohngesetz die vergangene Entwicklung der Tariflöhne gelten. Nach dem Tarifindex des Statistischen Bundesamtes stiegen die Tariflöhne in den Jahren 2014 und 2015 insgesamt um 5,5%. Demnach müsste der Mindestlohn auf etwa 9 exteuro angehoben werden. Darüber hinaus wäre zu prüfen, ob ein solches Mindestlohnniveau tatsächlich den im Mindestlohngesetz geforderten "angemessenen Mindestschutz der Arbeitnehmerinnen und Arbeitnehmer" gewährleistet.
urn:nbn:de:101:1-201602176403
Keywords: 330